2016
DOI: 10.1080/10967494.2016.1160012
|View full text |Cite
|
Sign up to set email alerts
|

Policy Target Populations and Public Participation in Agency Decision Making

Abstract: Why are some government agencies more open to public input than others? Although many agree about the normative desirability of involving citizens in administrative decision making, there is significant variation across agencies in the extent of public participation. This article investigates the conditions under which public managers solicit greater public participation. We argue that, in addition to normative rationales, participation also serves instrumental considerations related to agency constituency. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Research has demonstrated that public officials’ attitudes toward public participation are an important element in the success of participatory decision‐making efforts (Denhardt and Denhardt ; Hatcher ; Liao and Schachter ; Neshkova and Guo ; Yang ; Yang and Callahan ; Zhang and Yang ). However, research on the determinants of public officials’ attitudes toward public participation is limited (exceptions e.g., Liao and Schachter ; Ianniello et al ).…”
Section: What Determines Officials’ Attitudes About Public Participatmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that public officials’ attitudes toward public participation are an important element in the success of participatory decision‐making efforts (Denhardt and Denhardt ; Hatcher ; Liao and Schachter ; Neshkova and Guo ; Yang ; Yang and Callahan ; Zhang and Yang ). However, research on the determinants of public officials’ attitudes toward public participation is limited (exceptions e.g., Liao and Schachter ; Ianniello et al ).…”
Section: What Determines Officials’ Attitudes About Public Participatmentioning
confidence: 99%
“…Central to the success of participatory processes are public officials who are willing to engage with citizens (Hatcher ; Hong ; Ianniello et al ; Liao and Schachter ; Yang ; Yang and Callahan ). Public officials are involved in all stages of the participatory process, and they influence how participation takes place and how public inputs are put into practice (Bryson et al ; Buckwalter ; Neshkova and Guo ; Yang and Callahan ). According to Yang and Callahan (, 250), “it stands to reason that favourable attitudes toward public participation may positively affect administrative decisions to include citizens in administrative processes” (see also Hong ; Yang and Callahan ; Zhang and Yang ).…”
mentioning
confidence: 99%
“…This mirrors Schneider and Ingram's (1993) construction visuals, which show that while minorities tend to have high political power, society at-large mostly view them negatively. It is the same case for follow-up work (Neshkova & Guo, 2016) scholars have done when examining Schneider and Ingram's (1993) work and applying it to empirical studies involving citizen participation.…”
Section: Racementioning
confidence: 99%
“…However, an empirical study from Neshkova and Guo (2016) showed that whether or not a group is viewed favorably has a greater effect than power. They examined the four agencies' constituencies that would fall under one of the four different combinations from Schneider and Ingram (1993) of power and public image (Example:…”
mentioning
confidence: 99%
See 1 more Smart Citation